Pengaruh Gaya Kepemimpinan Transformasional, Lingkungan Kerja, Dan Pengembangan Sumber Daya Manusia Terhadap Kinerja Karyawan BUMdes Mitulungi Desa Tulungrejo - Amalia, Dian; Khalikussabir, Khalikussabir; Slamet, Afi Rachmat (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstact This study aims to analyze the influence of transformational leadership style, work environment, and human resource development on employee performance at BUMdes Mitulungi in Tulungrejo Village. Aquantitative approach was used, with survey data collected via questionnaires distributed to 37 respondents, comprising all BUMdes employees. Data were analyzed using multiple linear regression to examine both simultaneous and partial effects of each independent variable on employee performance. The results indicate that transformational leadership, work environment, and human resource development simultaneously have a positive and significant impact on employee performance. Individually, each variable also shows a significant influence on performance improvement. These findings highlight the importance of leadership, a supportive work environment, and continuous HR development in enhancing productivity and organizational effectiveness at BUMdes Keywords: Transformational Leadership Style, Work Environment, Human Resource Development, Employee Performance, BUMdes